Acute Effects of Two Types of Dumbbell Exercise on Oxygenated Hemodynamic Concentration of Cerebral Activation in Healthy Young Male Adults: A Functional Near-Infrared Spectroscopy Study - Wang, Yana; Lü, Jiaojiao; Rong, Jifeng; Song, Linjie; Wang, Wei; Jiang, Yifan; Liu, Yu; Huang, Lingyan (Frontiers in Human Neuroscience, 2020)
Purpose. To examine cerebral cortical activation differences in the frontal cortex and parietal lobe during the performance of two types of dumbbell exercise. Methods. A total of 22 young healthy male adults (mean age, 23.8 ± 2.05 years; height, 1.75 ± 0.06 m; weight, 71.4 ± 8.80 kg) participated in a crossover design study that involved two experimental exercise conditions: momentum dumbbell and conventional dumbbell. Performance tasks included 10 10-second sets of single-arm dumbbell exercise, with a rest interval of 60 seconds between sets and a 5-minute washout period between conditions. The primary outcome was the cerebral concentrations of oxygenated hemoglobin (HbO2) in the frontal cortex and parietal lobe assessed during performance of both exercises using functional near-infrared spectroscopy. The secondary outcome was upper-limb muscle activation measured using surface electromyography. Outcome data were ascertained during exercise. Results. A significant between-condition difference in HbO2 was observed in the frontal and parietal regions with an increase in HbO2 during momentum, relative to conventional, dumbbell exercise (p < 0.05). Compared to conventional dumbbell exercise, performing a momentum dumbbell exercise led to a higher level of muscle activation in the anterior and posterior deltoids of the upper arm and in the flexor carpi radialis and extensor carpi radialis longus of the forearm (p < 0.05). However, no between-condition differences were found in the biceps and triceps brachii (p > 0.05). Conclusion: Dynamic, compared with conventional, dumbbell exercise resulted in higher hemodynamic responses and greater upper-limb muscle activation in young healthy adults. The findings of this study showed differential cortical hemodynamic responses during performance of the two types of dumbbell exercise with a higher activation level produced during momentum-based dumbbell exercise.